2016
DOI: 10.1371/journal.pntd.0004510
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Calflagin, a Flagellar Calcium-Binding Protein from Trypanosoma congolense

Abstract: BackgroundIdentification of species-specific trypanosome molecules is important for laboratory- and field-based research into epidemiology and disease diagnosis. Although Trypanosoma congolense is the most important trypanosome pathogen of cattle in Africa, no species-specific molecules found in infective bloodstream forms (BSF) of the parasites have been identified, thus limiting development of diagnostic tests.MethodsImmuno-mass spectrometric methods were used to identify a protein that is recognized by a T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It was previously hypothesized that Tc24 is located in the flagellar pocket of the parasite, [13,25,26] which would suggest that antibodies could bind to the trypomastigotes, possibly preventing cell invasion. However, in the broader field of trypanosomatids research, it has been shown that flagellar calcium-binding proteins are typically localized intracellularly on the flagellar membrane, [27,28] specifically anchoring to the inner leaflet of the flagellar membrane. [7,[29][30][31] In this case, a humoral response would unlikely be effective to prevent a trypomastigote from infecting host cells.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously hypothesized that Tc24 is located in the flagellar pocket of the parasite, [13,25,26] which would suggest that antibodies could bind to the trypomastigotes, possibly preventing cell invasion. However, in the broader field of trypanosomatids research, it has been shown that flagellar calcium-binding proteins are typically localized intracellularly on the flagellar membrane, [27,28] specifically anchoring to the inner leaflet of the flagellar membrane. [7,[29][30][31] In this case, a humoral response would unlikely be effective to prevent a trypomastigote from infecting host cells.…”
Section: Introductionmentioning
confidence: 99%